Metaldehyde treatability by dissolved air flotation combined with powdered activated carbon adsorption - Sanchez Lopez, Sara (Cranfield University, 2017)
The removal of metaldehyde to meet pesticide compliance limits in drinking water remains a challenge for water companies. A combined treatment of dissolved air flotation (DAF) and powdered activated carbon (PAC) was investigated as a treatment process for metaldehyde removal. Four different water sources were spiked with metaldehyde and treated using PAC. A PAC dose of 100 mg/L using a contact time of 20 minutes was required in order to effectively remove metaldehyde to the compliance concentrations for all of the water sources. The water quality was shown to affect the removal of metaldehyde through competition with NOM. Moreover, the PAC dosing position relative to the coagulant was studied regarding its impact on the removal of NOM and metaldehyde, the floc formation and the clarification efficiency. The simultaneous addition of coagulant and PAC resulted in the lowest removal of metaldehyde. The best removal was seen for dosing sequences of PAC/Coagulant and Coagulant/PAC. However, there were no significant differences between these two approaches. The sequence of addition of PAC/Coagulant was selected due to its better clarification results.
Keywords: Metaldehyde; Dissolved Air Flotation; Pesticide; Adsorption; Powdered Activated Carbon; Drinking Water